THE COMPARATIVE ANALYSIS OF GOLD, STOCKS, SWISS-FRANC, AND BITCOIN AS PORTFOLIO PERFORMANCE DURING COVID-19 PANDEMIC - Krisantana, Wayan Jonatan Satwika; Pratomo, Devanto S. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research is based on the phenomenon of new trend of investment during the pandemic. In the last few months, investing in stocks and cryptocurrency is trending in all social media platform. Investment is an asset or item acquired with the goal of generating income or appreciation. The researcher also interest about currency of Swiss nation or called Swiss-franc (CHF). It is because researcher join investment community called “Ternak Uang” and the owners (Timothy Ronald) told that during the pandemic, he switching some of asset portfolio to Swiss-franc in part of hedging investment. There are so many investment products, but this research focusing on four product which are Gold, Stocks (IDX 30), Swiss-franc, and Bitcoin. This research is quantitative research using the comparative method. This research uses time series data, the data collected from time to time on an object for the purpose of describing object development. In this study the type of data used is secondary data in the form of historical data of instrument. Then, the researcher using non-parametric statistical tests, i.e. Kruskall-Wallis test. The result show Bitcoin as an investment that provides the largest return assets, Based on significance value, every instrument also has a real difference risk, Swiss-franc is the highest performance in Sharpe and Jensen Ratio while in Treynor, bitcoin is the highest performance, and Based on significance value, every instrument also has a real difference Treynor and Jensen ratio between each other.